2021
DOI: 10.1111/gcb.15872
|View full text |Cite
|
Sign up to set email alerts
|

Detecting forest response to droughts with global observations of vegetation water content

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 160 publications
2
63
0
Order By: Relevance
“…Diurnal differences in backscatter during the dry season are dominated by transpiration losses. Long-term monitoring of these diurnal differences could provide insight into moisture availability and its influence on transpiration and vegetation functioning (Konings et al, 2021). Consistent with previous studies on the effect of drought on the backscatter signal over the Amazon forests (Frolking et al, 2011;Saatchi et al, 2013), a negative anomaly in backscatter was observed during the 2010 and 2015 drought; although this was minor for the moist forests, strong anomalies were observed in the Cerrado.…”
Section: Discussionsupporting
confidence: 87%
“…Diurnal differences in backscatter during the dry season are dominated by transpiration losses. Long-term monitoring of these diurnal differences could provide insight into moisture availability and its influence on transpiration and vegetation functioning (Konings et al, 2021). Consistent with previous studies on the effect of drought on the backscatter signal over the Amazon forests (Frolking et al, 2011;Saatchi et al, 2013), a negative anomaly in backscatter was observed during the 2010 and 2015 drought; although this was minor for the moist forests, strong anomalies were observed in the Cerrado.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, Konings & Gentine (2017) demonstrated that spatial variations in isohydricity could be derived from microwave estimates of vegetation water content. Conceivably these data may offer a pathway to better capture inter-and intraspecific variation in drought responses at the ecosystem scale, directly relevant to global models (please refer to also Konings et al (2021) for a review). Nevertheless, microwave estimates are coarse (> 25 km), hampering comparison with field-based hydraulic traits; therefore, if used to parameterise models, we could run the risk of conflating within-species vs among-species drought risk.…”
Section: Future Directionsmentioning
confidence: 99%
“…In many cases, substantial increases in resolution are possible with drone‐mounted instruments (e.g., SIF, Mohammed et al, 2019). The information provided by these platforms is sensitive to limitations and biases, which are well‐reviewed elsewhere (Fisher et al, 2020; Konings et al, 2021; Magney et al, 2020), and will continue to benefit from validation with flux tower data (e.g. Fisher et al, 2020; Sun et al, 2017), including novel strategies for fusing data across different scales of observation (see Section 3.3).…”
Section: Informing Nbcss With a Full Set Of Tools And Approachesmentioning
confidence: 99%
“…These next‐generation platforms include (a) solar‐induced fluorescence (SIF), which is physiologically related to the rate of photosynthesis (Magney et al, 2020), (b) column‐averaged atmospheric CO 2 which can be used for “inverse” estimates of land carbon fluxes (Wang et al, 2019), and (c) instruments for sensing ecosystem water stress (e.g., ECOSTRESS, Fisher et al, 2020, and microwave data on canopy water content, Konings et al, 2021). While the spatial resolution of these satellite products can be coarse, some are now available at scales that match those of individual farms (e.g., ECOSTRESS, Fisher et al, 2020), and the need for finer‐scale versions of other products has been clearly articulated (Konings et al, 2021). In many cases, substantial increases in resolution are possible with drone‐mounted instruments (e.g., SIF, Mohammed et al, 2019).…”
Section: Informing Nbcss With a Full Set Of Tools And Approachesmentioning
confidence: 99%